Exploring Factors Influencing Potential Writing Skill Deficiencies Among Students at SMA Khadijah: A Teacher's Insight Solution - Ubaidillah, Muhammad Farid (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research at SMA Khadijah investigates factors influencing potential writing skill deficiencies among students, addressing the critical need to enhance English proficiency in Indonesia's educational landscape. English, a compulsory subject in junior and senior high school, holds increasing importance, yet the nation's low proficiency index underscores pervasive challenges. Focused on SMA Khadijah, a Cambridge certification center, the study aims to uncover multifaceted influences on writing proficiency by examining social nuances, pedagogical approaches, and external elements. The primary objective is to discern specific challenges in idea generation, organizational structure, and language mechanics through the perceptive insights of English teachers. The research also explores correlations with demographic factors, collaborative efforts, and the impact of digital technologies on writing education. Employing a qualitative approach, the study engages grade 12 English teachers using purposeful sampling and semi-structured interviews, with data analysis conducted through descriptive coding. Results highlight the students' generally strong writing skills but reveal areas needing improvement. The teacher's insights emphasize language input, particularly in vocabulary, and propose language enrichment and collaborative strategies. The implications extend to curriculum design, teacher training, and instructional practices. Overall, this research contributes actionable insights to inform targeted interventions, fostering a dynamic learning environment and positive transformations in writing education at SMA Khadijah and beyond